STATISTIC INDICATORS OF THE ASSESSMENT OF RISK OF PRODUCTION OF GRAIN - Ludmila V. Benkovskaya (Статистика и экономика, 2016)
The essence of risk is considered from a position of statistical approach. The existing statistic indicators of risk are analysedand added with indicators of stability andinstability. The author developed a new integrated indicator of risk of productionof grain. Adequacy and objectivity of an integrated indicator of risk is proved withuse of multidimensional statistical methods. Set of statistic indicators of risk was systematized.